Obowiązki pasterskie biskupa diecezjalnego - Wroceński, Józef (Prawo Kanoniczne, 2008)
At the Canon Law presently being in vigor, a Diocesan Bishop is called a shepherd. His main task in a local church is a leadership of triply character: teaching, sanctifying, and guiding that is ruling. I consequence the legislator enumerates several duties in connection with this task, which could be called the pastoral duties. The author in his article has analyzed the rules regarding those duties. A diocesan bishop as a successor of the Apostles has a specific power in the local church, which is put in his charge, and for this reason he can undertake necessary pastoral actions which are in line with the Church’s universal mission. He also is a visible sign of the unity in the community of the people of God. The author has also analyzed several other factors which condition the value and efficiency of a diocesan bishop’s services.